KONTROL DIRI, PENDIDIKAN PENGELOLAAN KEUANGAN KELUARGA, PENGETAHUAN INKLUSI KEUANGAN SISWA PENGARUHNYA TERHADAP PERILAKU MENABUNG SISWA SMK SE KOTA KEDIRI - Ardiana, Meta (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed (1) to analyze the influence of self-control on the savings behaviors of students, (2) analyze the influence of family financial management education to saving behavior, (3) analyze the effect of students knowledge of financial inclusion on the saving behaviors of students, (4) analyze the influence of self control, family financial management education, students knowledge of financial inclusion on saving behavior of students SMK in Kediri. The population in this study is accounting students and banking students a total of 477 and a total sample of 211 students. The data collection techniques used were questionnaire and document. Analyze methode using multiple linear regression technique. The result showed that the self control, family financial management education, students knowledge of financial inclusion partially has positive significant effect on saving behaviors student SMK in Kediri. Self control, family financial management education, students knowledge of financial inclusion Simultaneously have positive significant effect on saving behaviors student SMK in Kediri